Analisis Soal HOTS dalam Latihan Buku Teks Cerdas Cergas Berbahasa dan Bersastra Indonesia Kelas 12 - Efendi, Fathan Rizki; Isnaeni, Hanifah Nurul; Saputra, Riski (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2025)
This study aims to analyse the application of Higher Order Thinking Skills (HOTS) in the ‘Let's Practise’ exercises in the Cerdas Cergas Berbahasa dan Bersastra Indonesia (Smart and Agile in Indonesian Language and Literature) textbook for Year 12. The study focuses on three higher cognitive levels in Anderson's Taxonomy, namely C4 (analysis), C5 (evaluation), and C6 (creation). This study uses a descriptive qualitative approach by analysing 79 questions based on operational verbs and linguistic task contexts. The reliability of the classification is ensured through an inter-rater reliability procedure by two independent assessors. The results showed that all questions were within the HOTS domain, with the following distribution: C4 in 32 questions (40.5%), C5 in 28 questions (35.4%), and C6 in 19 questions (24.1%). This distribution indicates the dominance of analytical skills, followed by evaluative and creative skills. Conceptually, these results emphasise the importance of integrating evaluation (C5) and creation (C6) skills in Indonesian language learning to develop students' critical and expressive literacy competencies. Practically, these findings provide a basis for teachers, textbook authors, and curriculum developers to review and rewrite practice questions so that the proportion and depth of HOTS, particularly at the evaluation and creation levels, are more optimal in supporting the development of students' higher-order thinking skills.